Arabic Language Training Program Management: Objectives and Benefits at Madrasah Tsanawiyah Kampar - izzatul mellati; Hakmi Wahyudi; Muthia Khairani; Anugrah Ilahi; Muhammad Auli Rahman (Universitas Islam Negeri Palopo, 2026)
This study examines the management of Arabic language training programs at Madrasah Tsanawiyah in Kampar Regency, with particular attention to program objectives and perceived benefits. The study aims to analyze how training objectives are formulated and how the programs contribute to students and institutions. A descriptive qualitative approach was employed, involving eight participants: two principals, two curriculum vice principals, two Arabic language teachers, and two students from MTsN 4 Kampar and MTs Muhammadiyah Pulau Rambai. Data were collected through semi-structured interviews, observations, and documentation, and analyzed using the Miles and Huberman interactive model. The findings indicate that the training programs aim to improve students’ Arabic communication skills, vocabulary mastery, Qur’anic comprehension, and religious character development. At MTsN 4 Kampar, approximately 80% of program objectives were achieved, while MTs Muhammadiyah Pulau Rambai faced constraints related to limited learning facilities and instructional media, which affected program effectiveness. Despite these challenges, the programs provided notable benefits, including increased student confidence, motivation, and speaking proficiency, as well as improvements in institutional learning quality. This study contributes by identifying gaps in objective-setting practices, particularly the absence of systematic needs analysis and measurable indicators, which are essential for effective Arabic language training program management